ORGANIZATIONAL COMMUNICATION AND ACCESSIBILITY RESOURCES IN THE DIGITAL ENVIRONMENT: INFLUENCES OF THE COVID-19 PANDEMIC ON BURGER KING BRASIL’S FACEBOOK - Luvizotto, Caroline Kraus [UNESP]; Magalhães, Guilherme Mori [UNESP] (Universidad de Lima, 2023)
One of the impacts of the COVID-19 pandemic has been the strengthening of the relationship between the public and organizations on the internet. For some time, changes were expected to occur in the digital environment, especially regarding the inclusion of people with disabilities. This study aims to assess how the intensification of forms of digital interaction during the COVID-19 pandemic has affected the use of accessible modes of communication with people with digital sensory management disabilities. While taking as our object the Facebook page of Burger King Brasil, we have turned our attention to similarities and dissonances between the forms of communication on social networks before (2019) and during the pandemic (2021). Both automatic and manual techniques to check web accessibility were deployed with a set of 12 publications on the page, 6 from each period studied. Upon completion of the study, findings suggest that barriers to accessibility—which are a consequence of social structures, such as ableism—have not been overcome. In fact, tensions do persist and are now adapted to the current scenario.
COMUNICACIÓN ORGANIZACIONAL Y RECURSOS DE ACCESIBILIDAD EN EL ENTORNO DIGITAL: INFLUENCIAS DE LA PANDEMIA DEL COVID-19 EN LA PÁGINA DE FACEBOOK DE BURGER KING BRASIL
Comunicação organizacional e recursos de acessibilidade no ambiente digital: influências da pandemia de COVID-19 no Facebook do Burger King Brasil
Keywords: accessibility; online communication; organizational communication; sensory deficiency; social networks